Global Cardiovascular Reserve Dysfunction in Heart Failure With Preserved Ejection Fraction - Borlaug, Barry A.; Olson, Thomas P.; Lam, Carolyn S.P.; Flood, Kelly S.; Lerman, Amir; Johnson, Bruce D.; Redfield, Margaret M. (Journal of the American College of Cardiology, 2010)
The purpose of this study was to comprehensively examine cardiovascular reserve function with exercise in patients with heart failure and preserved ejection fraction (HFpEF). Optimal exercise performance requires an integrated physiologic response, with coordinated increases in heart rate, contractility, lusitropy, arterial vasodilation, endothelial function, and venous return. Cardiac and vascular responses are coupled, and abnormalities in several components may interact to promote exertional intolerance in HFpEF. Subjects with HFpEF (n = 21), hypertension without heart failure (n = 19), and no cardiovascular disease (control, n = 10) were studied before and during exercise with characterization of cardiovascular reserve function by Doppler echocardiography, peripheral arterial tonometry, and gas exchange. Exercise capacity and tolerance were reduced in HFpEF compared with hypertensive subjects and controls, with lower VO2and cardiac index at peak, and more severe dyspnea and fatigue at matched low-level workloads. Endothelial function was impaired in HFpEF and in hypertensive subjects as compared with controls. However, blunted exercise-induced increases in chronotropy, contractility, and vasodilation were unique to HFpEF and resulted in impaired dynamic ventricular-arterial coupling responses during exercise. Exercise capacity and symptoms of exertional intolerance were correlated with abnormalities in each component of cardiovascular reserve function, and HFpEF subjects were more likely to display multiple abnormalities in reserve. HFpEF is characterized by depressed reserve capacity involving multiple domains of cardiovascular function, which contribute in an integrated fashion to produce exercise limitation. Appreciation of the global nature of reserve dysfunction in HFpEF will better inform optimal design for future diagnostic and therapeutic strategies.